1999
DOI: 10.1016/s0042-6989(99)00106-6
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of depth from opposite-contrast stimuli: transient system can, sustained system can’t

Abstract: The ability of observers to extract depth from opposite luminance-contrast-polarity stimuli was investigated. The stimuli consisted of two dichoptic-pairs of Gaussians, with one of the Gaussians in each pair having a positive contrast-polarity and the other a negative contrast-polarity. Stimulus durations ranging from 0.2 to 4 s were used. This range of durations was employed to reveal stereo mechanisms that were preferentially sensitive to transient or sustained stimuli. Stimuli were presented in a raised-cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Given the small delay introduced by the stereogoggles (10 ms) we predicted that, if depth had been perceived, it would have been in the reversed direction [19]. Secondly, the perception of depth in anti-correlated stimuli has been associated with processing in the transient system [33]. This system depends on the presence of information at high temporal frequencies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the small delay introduced by the stereogoggles (10 ms) we predicted that, if depth had been perceived, it would have been in the reversed direction [19]. Secondly, the perception of depth in anti-correlated stimuli has been associated with processing in the transient system [33]. This system depends on the presence of information at high temporal frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…This system depends on the presence of information at high temporal frequencies. Pope et al [33] argued that the spatial frequency tuning of the transient system makes it unsuitable for the detection of disparity in random dot stereograms. Here, we found no perception of depth in ACRDS with either brief (80 ms) or more sustained (up to 400 ms) presentations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have shown that anticorrelated images produce no sensation of depth (Julesz 1971;Cogan et al 1993;Cumming et al 1998). Pope et al (1999) concluded that spatially complex stimuli, like dense anticorrelated RDSs, appear to be processed exclusively by the sustained system, which cannot match opposite-contrast stimuli (Howard and Rogers 2002). Our stimuli were sustained with respect to the presentation times.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Clifton Schor and colleagues have conducted a systematic characterization of our sensitivity to depth from transient and sustained disparity (Schor et al, 2001(Schor et al, , 1998(Schor et al, , 1984Edwards et al, 2000Edwards et al, , 1999aPope et al, 1999). These studies have shown different 1) spatial tuning, 2) tendency to depth-alias, 3) orientation tuning, 4) sensitivity to spatial envelope size, and 5) tolerance for opposite polarity, for long vs. short duration depth stimuli.…”
Section: Functional Organizationmentioning
confidence: 99%